2021
DOI: 10.1016/j.jcot.2021.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary fixation of fibula fractures: A systematic review

Abstract: Introduction: Distal fibula fractures are common injuries that often require open reduction internal fixation. Intramedullary fixation of the fibula has been used historically, and interest has been renewed somewhat recently, although there is limited data assessing outcomes after intramedullary fibular fixation. The purpose of this study was to systematically evaluate the literature as it relates to the clinical and functional outcome after fibular fracture fixation using an intramedullary device. Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Nail fixation has shown promising results in the treatment of ankle fractures; however, the evidence is mainly based on small case series and retrospective studies. A recent systematic review by Bäcker et al 28 reported a large variation among the studies which were included, preventing definitive conclusions on the preferred form of treatment. A minimally invasive technique has been considered beneficial in patients with compromised soft-tissues and a high risk of wound complications.…”
Section: Discussionmentioning
confidence: 99%
“…Nail fixation has shown promising results in the treatment of ankle fractures; however, the evidence is mainly based on small case series and retrospective studies. A recent systematic review by Bäcker et al 28 reported a large variation among the studies which were included, preventing definitive conclusions on the preferred form of treatment. A minimally invasive technique has been considered beneficial in patients with compromised soft-tissues and a high risk of wound complications.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a less invasive, percutaneous approach and intraosseous fixation have been made possible by the use of intramedullary devices, in which rotation is controlled by distal screws. Thus, the use of a fibular intramedullary nail is currently a common, low risk treatment option for ankle fractures 21,22 , fibular fractures linked to mid-and distal-tibia fractures, and pilon fractures 10,19,23,24 . One benefit of fibular intramedullary fixation is the ability to achieve stability with a smaller incision, which may allow for quicker definitive steadiness in patients with significant edema or fracture blisters.…”
Section: Discussionmentioning
confidence: 99%
“…One benefit of fibular intramedullary fixation is the ability to achieve stability with a smaller incision, which may allow for quicker definitive steadiness in patients with significant edema or fracture blisters. Additionally, the intramedullary location may result in a lower incidence of hardware removal and peroneal tendon irritation 24 investigated. To further corroborate this findings, a long-term randomized controlled trial research with a larger significant patient and control group and different fixation techniques should be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates open reduction and visualization of the fibula and extent of fracture. Intramedullary nailing is an increasingly used technique for treating these fractures, offering the advantages of smaller incisions for open reduction and nail insertion as well as less soft tissue dissection and preservation of periosteal blood supply, at the price of increased implant cost [4][5][6]. However, certain circumstances, such as comminuted fractures or revision surgeries with previous hardware and screw tracts, can cause the guidewire to deviate resulting in an inability to pass the guidewire or malreduction of the fibula and syndesmosis.…”
Section: Introductionmentioning
confidence: 99%